Point-of-Care Cardiac Ultrasound Training Programme: Experience from the University Hospital Hradec Králové - Petr Grenar; Jiří Nový; Karel Mědílek; Martin Jakl (Emergency Medicine International)
Point-of-care ultrasound examinations performed by physicians of different specialties are a rapidly growing phenomenon, which has led to a worldwide effort to create a standardised approach to ultrasound examination training. The implementation of emergency echocardiography by noncardiologists is mainly aimed at the standardisation of the procedure, a structured training system, and an agreement on competencies. This article summarises the current training programmes for nonechocardiographers at the University Hospital in Hradec Králové. In cooperation with cardiologists specialised in cardiac ultrasound (ECHO), an extended acute echo protocol dedicated to emergency department physicians was developed and validated in daily practice. According to our retrospective evaluation, after one year of clinical practice, we can confirm that point-of-care ultrasound examinations performed using the standardised limited echo protocol are safe and accurate. The observed concordance with comprehensive ECHO was 78%. This trial is registered with NCT05306730.